Case definitions for onchocerciasis-associated epilepsy and nodding syndrome: A focused review. (April 2023) - Van Cutsem, G.; Siewe Fodjo, J.N.; Dekker, M.C.J.; Amaral, L.J.; Njamnshi, A.K.; Colebunders, R.
Highlights: Onchocerciasis-associated epilepsy (OAE) is a public health concern in Africa. OAE is responsible for a considerable yet preventable burden of disease. An easy-to-use case definition of OAE is needed mainly for epidemiological purposes. An OAE case definition would help to estimate the true onchocerciasis disease burden. The presence of OAE in a community suggests high ongoing onchocerciasis transmission. Abstract: Onchocerciasis-associated epilepsy (OAE) is an important but neglected public health problem in onchocerciasis-endemic areas with insufficient or inadequate onchocerciasis control. Hence, there is a need for an internationally accepted, easy-to-use epidemiological case definition of OAE to identify areas of high Onchocerca volvulus transmission and disease burden requiring treatment and prevention interventions. By including OAE as a manifestation of onchocerciasis, we will considerably improve the accuracy of the overall onchocerciasis disease burden, which is currently underestimated. Hopefully, this will lead to increased interest and funding for onchocerciasis research and control interventions, notably the implementation of more effective elimination measures and treatment and support for affected individuals and their families.